2018
DOI: 10.20448/journal.522.2018.42.137.145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Training Program to Promote the Knowledge and Awareness of Prospective Preschool Teachers on Emotional Neglect and Abuse

Abstract: The aim of the study was to investigate the effect of the " Training Program to Promote The Knowledge and Awareness of Prospective Preschool Teachers" developed to promote the knowledge and awareness of prospective preschool teachers concerning emotional neglect and abuse. The study group comprised a total of 120 prospective teachers (60 prospective teachers in the experimental group and 60 prospective teachers in the control group) attending Cumhuriyet University, Faculty of Education, Department of Preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Similar results were reported by Fagan and Stevenson. 15 In studies by Brown and Bhavnagri 25 education helped to reduce strict discipline in parents, which is congruent with the present study. A study performed by Kim and Kim 26 revealed that fathers' attitudes to child-rearing improved as a result of education offered to them.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar results were reported by Fagan and Stevenson. 15 In studies by Brown and Bhavnagri 25 education helped to reduce strict discipline in parents, which is congruent with the present study. A study performed by Kim and Kim 26 revealed that fathers' attitudes to child-rearing improved as a result of education offered to them.…”
Section: Discussionsupporting
confidence: 91%
“…In a study carried out by Kanak in Turkey, the educational intervention offered to adults was found to improve knowledge and awareness of child emotional abuse and neglect. 15 Similarly, 17 offered an education program to parents and found a significant decrease in scores for possible child abuse in parents provided with the education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations